1998
DOI: 10.1016/s0891-5849(97)00437-1
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Dismutase in Patients With Chronic Hepatitis C Virus Infection

Abstract: Abstract-It has been reported that hepatitis C virus (HCV) may cause oxidative stress in infected cells. Patients with chronic hepatitis C exhibit an increased production of tumor necrosis factor-␣ (TNF␣), a cytokine that can produce oxidative stress by stimulating the generation of reactive oxygen species (ROS). Cell defense against ROS includes overexpression of Mn-superoxide dismutase (SOD), an inducible mitochondrial enzyme. To investigate cell defense against oxidative stress in HCV infection, we analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
64
0
3

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 110 publications
(71 citation statements)
references
References 34 publications
4
64
0
3
Order By: Relevance
“…Increased SOD activity appears to be an adaptive response to increased generation of superoxide ions (29). Thus, our findings support the existence of oxidative stress in PBMC from patients with chronic HCV infection and are in agreement with previous data from our group showing increased Mn-SOD mRNA values in PBMC from these patients (16).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Increased SOD activity appears to be an adaptive response to increased generation of superoxide ions (29). Thus, our findings support the existence of oxidative stress in PBMC from patients with chronic HCV infection and are in agreement with previous data from our group showing increased Mn-SOD mRNA values in PBMC from these patients (16).…”
Section: Discussionsupporting
confidence: 93%
“…In addition to inflammatory mediators, oxidative stress can also be produced as a direct consequence of viral replication. In this respect it should be considered that HCV infects not only hepatocytes but also lymphocytes and monocytes (14,16,34), and thus it can cause direct cytopathic effects in the liver as well as in lymphoid cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,20 Oxidative stress is considered to contribute to the pathogenesis of HCV-infected patients. 21 Additionally, the expression of either the entire polyprotein or the nonstructural proteins of HCV has been associated with the generation of reactive oxygen species. 22,23 Our experiments showed that localization of TJ-associated proteins was altered in cells harboring genomic but not subgenomic replicons.…”
Section: Discussionmentioning
confidence: 99%